2021
DOI: 10.31246/mjn-2020-0083
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of hospital-acquired malnutrition in children: A study in a rural hospital of West Borneo, Indonesia

Abstract: Introduction: Hospital-acquired malnutrition (HAM) is prevalent among hospitalised children in developing countries. This condition relates to worse clinical outcomes, prolongs length of stay in hospitals, and increases mortality. A multidisciplinary approach should be performed to prevent and manage this problem. However, HAM is often underdiagnosed, especially in rural hospitals with limited human resources. This study aims to delineate the risk factors of HAM among hospitalised children in a rural hospital.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Underlying disease and nutritional status were significant risk factors for the occurrence of HM in our study subjects. These findings support a previous study conducted in several hospitals in Bali and West Borneo, which reported that a high risk of HM was significantly associated with chronic, moderate-to-severe disease and nutritional status (Sidiartha, 2018;Prasetya, Haryanti & Nurani, 2021). Malnutrition is a pathological condition affecting most children.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Underlying disease and nutritional status were significant risk factors for the occurrence of HM in our study subjects. These findings support a previous study conducted in several hospitals in Bali and West Borneo, which reported that a high risk of HM was significantly associated with chronic, moderate-to-severe disease and nutritional status (Sidiartha, 2018;Prasetya, Haryanti & Nurani, 2021). Malnutrition is a pathological condition affecting most children.…”
Section: Discussionsupporting
confidence: 90%
“…This current study revealed that HM was more common in toddlers (50.9%). A previous study reported that age <5 years old was a risk factor of HM in children hospitalised in a rural hospital (Prasetya, Haryanti & Nurani, 2021). Similarly, another study found that children under 60 months old were more likely to suffer from hospital-acquired malnutrition (Spagnuolo et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
“…deficiencies can increase the risk of serious health complications, such as anemia, osteoporosis, and heart failure. [1][2][3][4] A nasogastric tube (NGT) is an option for providing enteral nutrition to children who have difficulty eating.…”
mentioning
confidence: 99%